Identificación de guanacos y llamas en el registro arqueológico de los Andes centro-sur con técnicas de morfometría geométrica - Anahí Hernández; Pablo Mercolli (Antípoda: Revista de Antropología y Arqueología)
South American camelids were essential to the subsistence of pre-Hispanic Andean populations. In Northwestern Argentina (NOA), both wild and domesticated large camelid species—guanaco and llama—have been present in the archaeological record since the early Late Holocene. Differentiating between their remains is crucial for understanding the dietary contributions of wild and domesticated resources to these populations. Traditional morphometric methods, often used to distinguish camelid species by size, encounter challenges due to the overlapping body sizes of guanacos and llamas. This study, conducted between 2019 and 2024, analyzes a sample of first phalanges from guanacos and llamas at the Quebrada del Cementerio site (Quebrada de Humahuaca, Jujuy, Argentina) using two-dimensional geometric morphometrics techniques. The goal is to distinguish these camelid phalanges by shape, aiding in accurate taxonomic identification. The results were compared with previous size-based studies using traditional morphometric techniques, revealing a predominance of llamas over guanacos, consistent with prior osteometric assessments. However, traditional morphometry lacks precision in identifying intermediate-sized specimens, which may represent either large guanacos or small llamas. Geometric morphometrics, on the other hand, allows for a more precise taxonomic identification of these specimens, complementing traditional methods. This approach refines the representation frequencies of both species, showing a slightly lower percentage of llamas and a higher percentage of guanacos than previously estimated by osteometric analysis. The findings offer a more detailed view of the role these species played in the diets of human populations in Quebrada during the Late Holocene.